Establishing comparability and compatibility in the purity assessment of high purity zinc as demonstrated by the CCQM-P149 intercomparison. (19th February 2018) - Vogl, Jochen; Kipphardt, Heinrich; Richter, Silke; Bremser, Wolfram; del Rocío Arvizu Torres, María; Lara Manzano, Judith Velina; Buzoianu, Mirella; Hill, Sarah; Petrov, Panayot; Goenaga-Infante, Heidi; Sargent, Mike; Fisicaro, Paola; et al.
Abstract: For the first time, an international comparison was conducted on the determination of the purity of a high purity element. Participants were free to choose any analytical approach appropriate for their institute's applications and services. The material tested was a high purity zinc, which had earlier been assessed for homogeneity and previously used in CCQM-K72 for the determination of six defined metallic impurities. Either a direct metal assay of the Zn mass fraction was undertaken by EDTA titrimetry, or an indirect approach was used wherein all impurities, or at least the major ones, were determined and their sum subtracted from ideal purity of 100%, or 1 kg kg −1 . Impurity assessment techniques included glow discharge mass spectrometry, inductively coupled plasma mass spectrometry and carrier gas hot extraction/combustion analysis. Up to 91 elemental impurities covering metals, non-metals and semi-metals/metalloids were quantified. Due to the lack of internal experience or experimental capabilities, some participants contracted external laboratories for specific analytical tasks, mainly for the analysis of non-metals. The reported purity, expressed as zinc mass fraction in the high purity zinc material, showed excellent agreement for all participants, with a relative standard deviation of 0.011%. The calculated reference value, w (Zn)  =  0.999 873 kg kg −1, was assigned an asymmetric combined uncertainty of  +0.000 025 kg kg −1 and  −0.000 028 kg kg −1 . Comparability amongst participating metrology institutes is thus demonstrated for the purity determination of high purity metals which have no particular difficulties with their decomposition/dissolution process when solution-based analytical methods are used, or which do not have specific difficulties when direct analysis approaches are used. Nevertheless, further development is required in terms of uncertainty assessment, quantification of non-metals and the determination of purity of less pure elements and/or for those elements suffering difficulties with the decomposition process.